Quelle « Base » pour les approches ascendantes ? Une redéfinition de l’approche participative dans la construction des politiques de gestion des ressources naturelles en Guinée maritime - Pascal Rey (Éditions en environnement VertigO, 2009)
In Coastal Guinea, natural ressources management is clearly assumed by traditional powers : they have a real consideration for their sustainability. The limits of the administration action at a local scale, as the ignorance of the autochton’s practices, are all the more prejudicial. As the Government doesn’t have a local presence, neither a good knowledge of the local land management modalities, it would be a pragmatic choice to consider the local structure which follows the same goal : to maintain the ressources sustainability. Therefore, we should ask ourselves how to integrate the local populations in the construction of the environmental policies.